DEVELOPING ENGLISH LEARNING MATERIALS FOR YOUNG LEARNERS BASED ON NEEDS ANALYSIS AT MTSN MODEL MAKASSAR - Ali Mubar, Miftahul Khair Nur (ETERNAL (English, Teaching, Learning, and Research Journal), 2015)
The main objective of this study was to develop English speaking materials especially speaking as additional learning sources. This research was conducted at MTsN Model Makassar in academic year 2014/2015. In this research, the population was the third grade students. There were 20 students as the respondents of 19 questionnaire questions.The design used by researcher in this research was Research and Development (R&D). R&D is a name of one research designs involving the classroom problems, studying recent theories of educational product development, developing the educational products, validating the product to experts, and field testing the product (Latif, 2012). The researcher adopted ADDIE Model. ADDIE is acronym of Analysis, Design, Development, Implementation, and Evaluation.The result of the research showed that, the third grade students of MTsN Model Makassar want English materials especially speaking materials based on their needs. The existing materials that they used in learning still have many weaknesses. Then, these findings become the basic for the researcher to develop English learning materials especially for speaking.Finally, The English learning materials for students called speaking materials consist of six rules as main topic and 18 activities to improve students’ speaking ability. The materials presented in 24 pages.